2022
DOI: 10.3389/fonc.2022.966051
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3-dimensional printed simulation surgical training models for endoscopic endonasal and transorbital surgery

Abstract: BackgroundEndoscopic skull base surgery (ESBS) is complex, requiring methodical and unremitting surgical training. Herein, we describe the development and evaluation of a novel three-dimensional (3D) printed simulation model for ESBS. We further validate the efficacy of this model as educational support in neurosurgical training.MethodsA patient-specific 3D printed simulation model using living human imaging data was established and evaluated in a task-based hands-on dissection program. Endoscopic endonasal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Fourteen studies of simulation with synthetic models were identified. 11,15,[27][28][29][30][31][32][33][34][35][36][37][38] 27,[29][30][31]35,36 Oyama et al described one of the most complete synthetic simulation models, in which the anterior, middle, and posterior fossa could be accessed through both sagittal and coronal plane approaches. 31 [29][30][31][32]35,36,38 whereas Wen et al enhanced the training of sellar tumor resection by curetting the inner content of an egg.…”
Section: Synthetic Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies of simulation with synthetic models were identified. 11,15,[27][28][29][30][31][32][33][34][35][36][37][38] 27,[29][30][31]35,36 Oyama et al described one of the most complete synthetic simulation models, in which the anterior, middle, and posterior fossa could be accessed through both sagittal and coronal plane approaches. 31 [29][30][31][32]35,36,38 whereas Wen et al enhanced the training of sellar tumor resection by curetting the inner content of an egg.…”
Section: Synthetic Modelsmentioning
confidence: 99%
“…11,15,[27][28][29][30][31][32][33][34][35][36][37][38] 27,[29][30][31]35,36 Oyama et al described one of the most complete synthetic simulation models, in which the anterior, middle, and posterior fossa could be accessed through both sagittal and coronal plane approaches. 31 [29][30][31][32]35,36,38 whereas Wen et al enhanced the training of sellar tumor resection by curetting the inner content of an egg. 28 In addition, Shah et al aimed to produce a model that assisted in identifying patient-specific sphenoid sinus landmarks and tested the participant's acquired knowledge in the operating room.…”
Section: Synthetic Modelsmentioning
confidence: 99%
See 3 more Smart Citations